Self-control using Traffic Lights Toolkit for Academic Success - Munna, Afzal Sayed (Advances in Social Sciences Research Journal, 2021)
The term traffic light refers to automatically operated coloured light those help control the traffic. In this piece of writing the term has been used to reflect from the day-to-day practice how one can make use of self-control for their academic success. The aim of introducing the traffic light toolkit in higher education is to ensure that there is an effective way to monitor and improve the learning experience. It was evidenced from previous use that the traffic light system encourage reflection and help continue ongoing self-assessment and improve academic performance level.